2020
DOI: 10.15294/elt.v9i1.36461
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ reinforcement and students’ perception to the teachers in English classroom

Abstract: The study focuses on the positive reinforcement that is used by the teachers in each class and students’ perception towards reinforcement itself. This research involved two English teachers and two different classes of year ten students in SMA Kristen YSKI Semarang. To describe the use of reinforcement by the teachers, their teaching process were recorded and observed. Questionnaire and interview were done at the end of the lesson to describe how the students perceive reinforcement. This study is qualitative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In this study, the students also obtained another improvement such as their participation, attendance, motivation and behavior. A study from Lestari (2020) supported the statement. In the study, all of the students agreed about the importance and usefulness of reinforcement in the classroom.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In this study, the students also obtained another improvement such as their participation, attendance, motivation and behavior. A study from Lestari (2020) supported the statement. In the study, all of the students agreed about the importance and usefulness of reinforcement in the classroom.…”
Section: Discussionmentioning
confidence: 59%
“…Burnett and Mandel (2010) stated that students who reported that their classroom was a positive environment reported a positive relationship with their teacher and perceived that their teacher gave them a great deal of ability feedback. In line with Lestari (2020), she found that the students all agreed that reinforcement positively helped them in the classroom. As result, the students may achieve a better score as the study conducted by Pratiwi (2015) which showed that more than half of students agreed it helped them improving students' grade.…”
Section: Perceptionmentioning
confidence: 63%
“…In the context of this research, most students around the research area seemed not really interested in English. It is because they lack of English language skills, have few experiences in using English in their daily life, and are not expected to use it in their future (Astuti in Lestari, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have conducted research dealing with the implementation of reinforcement in the teaching-learning process to different participants with different subjects. For example, Maslichah & Haryono (2013) did it to Junior High School students in teaching Mathematic and Lestari (2020) did it to Senior High School students in teaching English. All of the researches showed the same results that the students give a positive response to any kind of reinforcement given by the teacher during the teaching-learning process.…”
Section: Introductionmentioning
confidence: 99%